Lourdes, a major religious tourism destination, between crisis and transition? - Nathalie Jarraud; Sylvie Clarimont (Via@)
The obsolescence of some tourism sites has been researched and modelled by the geographers R.W. Butler and M. Chadefaud who applied the concept of a product’s life cycle. This approach to the evolution of destinations has been adapted to Lourdes, a major religious tourism destination. By disrupting the system in Lourdes, the COVID-19 crisis could accelerate the transformation of the destination and facilitate the transition. From a diachronic and synchronic viewpoint, this paper gives a wider perspective to the current crisis. Although the Sanctuary is introducing some innovative concepts, those innovations fall more within a logic of “adaptation-resilience” than a transformation process. These initiatives are not universally welcomed by local tourism professionals, who find it difficult to consider a new approach to the destination. So far, the crisis seems to have exacerbated tensions among the tourism stakeholders in Lourdes rather than federating their energies around a common project of transition towards a more sustainable tourism model.